FREQUENCY, SEASONAL VARIATION AND TREATMENT OUTCOME OF MALARIA IN PANJGUR, PAKISTAN - Akram, Sumera; Khan, Muhammad Ahmed; Usman Shah, Hassan Bin (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine frequency, types, seasonal variation and treatment outcome of malaria in Panjgur, Pakistan. Methodology: Total 815 cases of malaria, reported at Frontier Corps Medical Centre Panjgur, from January to December 2018 were included in this cross sectional study. Diagnosis of malaria was made on clinical symptoms and laboratory evidence of plasmodium parasite. Anti-malarials were administered according to the type of plasmodium. The data was entered and analyzed with SPSS version 20. Percentages were used to express frequencies. Chi square test was used to analyze qualitative variables. P value of â‰¤ 0.05 was considered significant. Results: Age range of cases was from 2 to 63 years. Mean age was 24.89 + 11.08 years. There were 653 male cases (80.1%) and 162 females (19.9%). Out of 815, 653 (84.5%) were cases of vivax malaria, 87 (10.7%) falciparum malaria and 37 (4.5%) were mixed malaria (both vivax and falciparum). Majority of cases were admitted from March to August months. Out of total 691 cases of vivax malaria, 93.34% were sensitive and 6.66% were resistant to chloroquine. They were sensitive to Artemether plus lumefantrene. Conclusion: Malaria is still a significant problem in remote areas of Pakistan. Vivax malaria is most common variety followed by falciparum and mixed malaria. Majority of cases were seen from March to August. Plasmodium vivax has good sensitivity to chloroquine but in few resistant cases combination anti-malarial drugs has to be used for treatment.